IMMU-22. Safely targeting GD2 in thalamic diffuse midline glioma with mRNA CAR T cells. (3rd June 2022) - Foster, Jessica; Griffin, Crystal; Stern, Allison; Madsen, Peter; Storm, Phillip; Resnick, Adam
Abstract: Chimeric antigen receptor (CAR) T cells targeting the disialoganglioside GD2 have shown promise as a therapeutic for diffuse midline glioma (DMG). However, prior studies raised significant concerns of neurotoxicity and fatality when using virally transduced CAR T cells against midline thalamic tumors. Building upon our prior work optimizing mRNA for use in CAR T cells (Hum Gen Ther, 2019), we hypothesized repeated dosing of transient GD2-directed mRNA CAR T cells could be employed for safe and effective treatment of thalamic DMG. GD2-directed CAR T cells were created using mRNA encoding the 14G2a single chain variable fragment paired with 41BB and CD3-zeta co-stimulatory domains and transfected into human T cells. CAR T cells were tested against the murine thalamic DMG xenograft 7316-6349 via locoregional delivery with an indwelling infusion catheter for repeated dosing. The previously reported fatal neurotoxicity observed in mice using lentiviral CAR T cells could be recapitulated with aggressive dosing. Four doses of 5 x 10 6 mRNA CAR T cells delivered intratumorally twice a week resulted in median overall survival of 9 days for GD2-treated mice compared to >30 days for CD19-treated controls (p<0.01). This toxicity could be avoided by decreasing the dose and timing of infusions to 2 x 10 6 mRNA CAR T cells delivered once weekly. Bioluminescent imaging showed regression of tumor in GD2-treated mice compared to CD19-treated controls (radiance fold change -3 x10 6 versus +20x10 6 p/sec/cm2/sr, p<0.01). Notably, non-tumor bearing mice treated with GD2-directed CAR T cells quickly developed fatal neurotoxicity within 14 days, suggesting on-target/off-tumor effect of the CAR T cells and a very narrow therapeutic window in the brain. These data highlight the utility of titratable mRNA-based CAR T cell therapy for CNS tumors and establish GD2-directed mRNA CAR T cells as a safe and effective method for treating thalamic DMG.